Gendered Microaggression Inventory: Construction and Initial Validation - Yang, Yang; Carroll, Dorris W. (My University, 2016)
Microaggressions are nuanced forms of insulting, disrespectful communications that occur during everyday exchanges. They target individuals from a different identity groups (e.g., race, gender, religion, sex orientation, person with disability; Nadal, 2011, Sue et al., 2007; 2008). Microaggressions are often subtle and can take on both verbal and nonverbal formats. Most of the research literature on microaggressions theory has focused on racial/ethnic microaggressions (Pierce, Carew, Pierce-Gonzalez & Willis, 1978; Nadal, 2011; Sue et al., 2007). The prevalence of racial microaggression and/or subtle racial discrimination has been documented in educational settings (Harwood, Choi, Orozco, Browne Huntt, & Mendenhall, 2015; Sue, 2010), workplace (Deitch, Barsky, Butz, Chan, Brief, & Bradley , 2003) and clinical settings (Sue et al., 2007). Studies have repeatedly shown that racial microaggressions not only had negative impacts on individuals’ emotional and physical health, but affected performance and productivity negatively (Flores, Tschann, Dimas, Pasch, & de Groat, 2010; Lambert, Herman, Bynum, & Ialongo, 2009; Pieterse, Carter, Evans, & Walter, 2010; Wei, Alvarez, Ku, Russell, & Bonett, 2010).
Citation: Yang, Y. & Carroll, D. (2016, April). Gendered Microaggressions Inventory: Construction and initial validation. Paper presented at the annual meeting for the American Educational Research Association, Washington, D.C.